Heat Acclimatization Protects the Left Ventricle from Increased Diastolic Chamber Stiffness Immediately after Coronary Artery Bypass Surgery: A Lesson from 30 Years of Studies on Heat Acclimation Mediated Cross Tolerance - Pollak, Arthur; Merin, Gideon; Horowitz, Michal; Shochina, Mara; Gilon, Dan; Hasin, Yonathan (Frontiers in Physiology, 2017)
During the period of 1986-1997 the first 4 publications on the mechanical and metabolic properties of heat acclimated rat’s heart were published The outcome of these studies implied that heat acclimation, sedentary as well as combined with exercise training, confers long lasting protection against ischemic/reperfusion insult. These results promoted a clinical study on patients with coronary artery disease scheduled for elective coronary artery bypass operations aiming to elucidate whether exploitation of environmental stress can be translated into human benefits by improving physiological recovery. During the 1998 study, immediate-post operative chamber stiffness was assessed in patients acclimated to heat and low intensity training in the desert (spring in the Dead Sea, 17-33C) vs. patients in cold weather (spring in Jerusalem, (6-19C) via echocardiogram acquisition simultaneous with left atrial pressure measurement during fast intravascular fluid bolus administration. We showed that patients undergoing “heat acclimation combined with exercise training” were less susceptible to ischemic injury, therefore expressing less diastolic dysfunction after cardiopulmonary bypass compared to non-acclimated patients. This was the first clinical translational study on cardiac patients, while exploiting environmental harsh conditions for human benefits. The original experimental data are described and discussed in view of the past as well as the present knowledge of the protective mechanisms induced by Heat Acclimation Mediated Cross-tolerance.